Cover Picture: Voltammetry of Layered Black Phosphorus: Electrochemistry of Multilayer Phosphorene (ChemElectroChem 3/2015). Issue 3 (11th March 2015) - Wang, Lu; Sofer, Zdenek; Pumera, Martin
<x xml:space="preserve">Abstract</x> Can you spot a footprint? Layered black phosphorus has recently attracted immense interest, being called multilayer "phosphorene". The phosphorene structure and corresponding voltammogram are shown on the background of White Sands National Monument (New Mexico), where yucca grows in barren white sand. Multilayer phosphorene is prepared by chemical vapor deposition and the black phosphorus exhibits inherent electrochemistry in the sense that it is oxidizable. This study is a first step in the utilization of black phosphorus in electrochemical applications, as shown by M. Pumera et al. on p. 324 (DOI: 10.1002/celc.201402363).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>